The Dibenzyl Isoquinoline Alkaloid Berbamine Ameliorates Osteoporosis by Inhibiting Bone Resorption - Zhang, Chongjing; Zhong, Zeyuan; Sang, Weicong; Ghorbani, Farnaz; Ghalandari, Behafarid; Mohamadali, Marjan; Irani, Shiva; Qian, Zhi; Yi, Chengqing; Yu, Baoqing (Frontiers in Endocrinology, 2022)
Postmenopausal osteoporosis (PMOP) is a kind of primary osteoporosis that is characterized by decreased bone density and strength. Berbamine is a nonbasic quaternary benzylisoquinoline plant alkaloid that has been widely used in the clinic to treat leukopenia in China. We found that berbamine inhibited RANKL-induced osteoclastogenesis of bone marrow-derived macrophages (BMMs) in vitro, which mainly occurred in the middle phase and late phase. The gene and protein expression levels of osteoclast-related molecules, including CTSK, MMP-9, NFATc1, CD44 and DC-STAMP, were also downregulated by berbamine. In vivo, we treated PMOP mice with berbamine for 8 weeks and found that the extent of osteoporosis was alleviated significantly according to micro-CT scanning, hematoxylin-eosin staining, DC-STAMP immunohistochemical staining and TRAP immunohistochemical staining in the distal femurs of the mice. Our findings demonstrate that berbamine has an inhibitory effect on the osteoclastogenesis of BMMs and can prevent bone loss after ovariectomy in vivo. This study provides evidence that berbamine is a potential drug for the prevention and treatment of PMOP.